Surplus Labour, Social Structure and Rural to Urban Migration: Evidence from Indian Data - Amaresh Dubey; Richard Palmer-Jones; Kunal Sen (The European Journal of Development Research, Vol.18, No.1, March 2006, pp.86-104, 2006)
This paper examines the empirical implications of the Lewis Model with respect to the relationship between the phenomenon of surplus labour in rural areas and out-migration from these areas to urban areas. It does so by using a micro-economic data set of migrants and non-migrants for India. We find strong empirical support for the key prediction of the Lewis Model that rural-urban migration will be influenced by the existence of surplus labour in the rural areas where the migrants originate. We also find that the phenomenon of rural-urban migration is more complex than viewed within a simple Lewis framework. Social structure and the possession of human capital are important determinants of rural-urban migration - individuals from scheduled castes and scheduled tribes and those with little or no education are less likely to migrate to urban areas. Given that scheduled castes and scheduled tribe households along with households with low levels of educational attainment are more likely to be poor, our findings suggest that the poorer households from the surplus labour regions do not seem to migrate to the same extent as the richer ones.